Hip Capsular Repair Affect on Joint Laxity in Total Hip Arthroplasty - Boonruksa, Sirisak; Ruangthong, Nathee (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: Loss of tissue tension around the hip is a cause of hip dislocation. The shuck test is a simple intraoperative test for soft tissue tension. This study evaluated the soft tissue tightness around the hip joint after capsule repair and compared the joint tension resulting from different capsule repair approaches. Methods: Fifty-three patients underwent a non-cemented total hip replacement using image-free computer-assisted surgery. The patients were divided into the posterior and the anterolateral approach groups. After the hip was reduce, a computer navigation plan was devise to restore proper leg length. The shuck test was applied to determine the soft tissue tension before and after capsule repair. The leg length was recorded after hip reduction and the shuck test. Data from the computer navigation were collected for analysis. Results The results of this study showed that after the shuck test, the leg length increased by up to 5.98±1.75 mm. (6.73±1.64 mm. and 5.26±1.56 mm for the posterior and anterolateral approach, respectively). After capsule repaire, the leg was shortened by 4.78±1.31 mm. (5.42±1.10 mm. and 4.15±1.20 mm for posterior and anterolateral approach, respectively). The study found that the leg shortening from the posterior approach was significantly higher than the anterolateral approach (p-value <0.001). There were no hip dislocations in this series. Conclusions: Hip capsule repair improves the soft tissue tension around the hip joint. This helps reduce the risk of hip dislocation. Hip capsule repair using a posterior approach has a better outcome.